Efficacy of 20 min yoga module for reducing burnout among healthcare workers: protocol of randomised control trial and results of pilot study - Monika Pathania; Vartika Saxena; Bela Goyal; Apar Avinash Saoji; Vikas Upadhyay (BMJ Open Sport & Exercise Medicine)
Burnout among healthcare workers is a significant global concern that affects their well-being and professional efficacy. Yoga has shown promise in reducing burnout and improving mental health outcomes. However, due to their hectic schedules, healthcare workers often struggle to find time for self-care. A 20 min yoga module has been developed specifically for them to address this. So, this study aims to assess the efficacy of a specific 20 min yoga module in reducing burnout among healthcare workers. An open-label, two-arm, randomised controlled trial involving healthcare workers aged 20–35 years participating for 4 weeks. Exclusion criteria included recent illness, respiratory ailments, pregnancy, life-threatening medical conditions or physical inability to perform yoga. After randomisation of 108 participants, they will be equally allocated to either the yoga group (20 min yoga) or the control group (20 min medium-paced walking). The primary outcome will be burnout, whereas the secondary outcomes include stress, anxiety, selective attention and happiness. Data collection: at baseline and after 4 weeks of intervention, compliance is monitored via daily attendance records. Descriptive and inferential analyses will employ intention-to-treat and per-protocol analysis using SPSS 26.0. A study with 20 participants found that a 20 min yoga intervention significantly improved emotional exhaustion, depersonalisation, personal accomplishment, happiness and Spielberger’s State-Trait Anxiety/Six-letter cancellation test scores. Cortisol levels showed trends of reduction but were not significant. These results inform the upcoming main trial. Ethical approval is obtained from the Institutional Ethical Committee via letter number AIIMS/IEC/20/762. The trial findings will be shared through peer-reviewed publications and presentations at conferences. Trial registration number: CTRI/2021/01/030568; Clinical Trial Registry of India.